Novel biomarkers in preeclampsia risk assessment - Antonić, Tamara; Ardalić, Daniela; Vladimirov, Sandra; Marković, Gorica; Cabunac, Petar; Mihajlović, Marija; Miković, Željko; Stefanović, Aleksandra (Archives of Pharmacy, 2022)
Despite significant progress in improving pregnancy outcomes in recent decades, predicting the risk and treatment of preeclampsia are still major challenges in clinical practice. The aim of this study was to examine non-routine biomarkers in preeclampsia risk assessment. The study involved 90 women with high-risk pregnancies, 20 of whom developed preeclampsia by the end of pregnancy. Biochemical parameters were determined between the 12th and 13th weeks of gestation. The results of the study showed that women who later developed preeclampsia had higher concentrations of lathosterol, cholesterol synthesis marker (p